Rising Like a Phoenix from the Ashes: Fire-Proof Magnetically Retrievable Supraparticles with an Optical Fingerprint for Postmortem Identification of Products - Miller, Franziska; Wenderoth, Sarah; Wintzheimer, Susanne; Mandel, Karl (Advanced Optical Materials, 2022)
Counterfeit electronic products not only cause financial losses but also come with safety risks. The worst-case failure scenario certainly is a fire event. Since manufacturers are liable for damages and suffer image loss, fire-proof postmortem taggants are needed, enabling differentiation between originals and counterfeits even after a fire incident. This work presents such taggants: optomagnetic supraparticles (SPs), i.e., complex microscale particles composed of luminescent and magnetic nanoparticles (NPs) are generated. Their hybrid nature is pivotal, as magnetic separation can effectively remove the tags from light-absorbing fire debris, and a fire-proof identification (ID) fingerprint is based on ratiometric luminescence signals. To achieve thermally stable magnets, iron oxide (IO) NPs are wet-chemically coated with a SiO2-3-aminopropyltriethoxysilane (APTES) shell. Subsequently, these magnetic NPs are assembled with luminescent nanophosphors (lanthanide-doped calcium phosphate NPs with a SiO2-core) and SiO2-APTES spacer NPs by spray-drying to form hybrid SPs. The careful choice of type and ratios of the NPs and process parameters make it possible to achieve and precisely tune the desired functionality of the resulting fire-proof taggants. A proof-of-concept is demonstrated, in which the taggants are incorporated as additives into coatings and subjected to real fire simulations.
CRIS-Team Scopus Importer:2022-10-21
Keywords: fire-proof; ID tags; luminescent ID; magnetism at high temperature; oxidation-stable magnetism; postmortem ID; supraparticles